2019
DOI: 10.12928/telkomnika.v17i5.12193
|View full text |Cite
|
Sign up to set email alerts
|

A novel compact CPW tunable stop band filter using a new Z-DGS-resonator for microwave applications

Abstract: The paper presents a novel very compact CPW bandstop filter. The designed structure consists of one unit of new Z-DGS resonator, placed on top layer of ground plane between the input and output this structure, which is excited by 50-ohm coplanar line. The designed filter can be used in X-Band applications as the band stop can be shifted to any other desired frequency by tuning the length of the Z-DGS. The proposed filter topology has as benefits good performances in terms of wide stop-band rejection, low inser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Multiband filters are an essential circuit block in multiband wireless communication systems that was recently designed and widely used [9][15]. Multiband bandpass filters have garnered a lot of consumer interest as a result of the development and proliferation of multiservice wireless communication systems in a single device.…”
Section: Introductionmentioning
confidence: 99%
“…Multiband filters are an essential circuit block in multiband wireless communication systems that was recently designed and widely used [9][15]. Multiband bandpass filters have garnered a lot of consumer interest as a result of the development and proliferation of multiservice wireless communication systems in a single device.…”
Section: Introductionmentioning
confidence: 99%
“…The progression of research works on the DGSs in RF and microwave for the last 10 years have shown evidences of improvement towards design realizations and performances. DGS has several advantages on the circuit [12], unwanted frequency suppression [13]- [15], bandwidth enhancement of antennas [16], [17], size compactness [18], [19], high power handling capability [20], isolation in antenna designs [21]- [23], and compensating parasitic capacitance of switching element to improve isolation [24], [25].…”
Section: Introductionmentioning
confidence: 99%
“…Using the two sides of the ground provides additional miniaturization for structure. In both free etched area [9,10], witch here a rectangle DGS and loaded DGS [11,12], by entering the 'e' slot in etching area in the ground of CPW line, an electric and magnetic coupling can be implemented, which allows for an intelligible design of simple an miniaturized structures, such as this proposed low pass filter, and many other structures with the same procedure.…”
Section: Introductionmentioning
confidence: 99%